MALIGNANT ADNEXAL TUMORS OF SKIN: A SINGLE CENTER EXPERIENCE - BATOOL, F; LONE, UM; JAHANGIR, F; KHAN, FW; RATHORE, S (Biological and Clinical Sciences Research Journal, 2024)
Malignant adnexal tumors (MATs) of the skin are rare neoplasms derived from eccrine, apocrine, sebaceous, or follicular structures. Objective: To analyze the histopathological spectrum of malignant adnexal tumors of the skin, determine their histological subtypes, and assess the association of ulceration, perineural invasion (PNI), lymphovascular invasion (LVI), and surgical margins with tumor behavior. Methodology: This cross-sectional descriptive study was conducted at Chughtai Institute of Pathology, Lahore, from January 2024 to July 2024 and included 61 histologically confirmed cases of malignant adnexal tumors of the skin. Data were retrieved from pathology archives and reviewed for demographic, clinical, and histological parameters, including tumor subtype, site, margin status, ulceration, PNI, and LVI. Results: Of the 61 patients, 37 (60.7%) were male, and 24 (39.3%) were female, with the majority aged between 61 and 70 years (34.4%). The head and neck region was the most frequently involved site (63.9%), followed by the trunk (19.7%) and extremities (13.1%). Porocarcinoma was the most common subtype (60.7%), followed by sebaceous carcinoma (23.0%) and hid adenocarcinoma (9.8%). Ulceration was present in 23 cases (37.7%), per neural invasion in 9 (14.8%), and lymph vascular invasion in 7(11.5%). Significant associations were observed between tumor site and subtype (p=0.038), margin status and surgical procedure (p<0.001), and ulceration and subtype (p=0.008). N significant correlation was found between ulceration and other histopathological variables such as gender, site, PNI, LVI, or margin status(all p>0.05). Conclusion: Malignant adnexal tumors predominantly affect older males and most commonly arise in the head and neck region. Porocarcinoma is the leading histologic subtype, followed by sebaceous and hidradenocarcinoma. While ulceration is frequent, it does not correlate significantly with clinical or pathological factors, except tumor subtype. Complete excision with negative margins remains the key to reducing recurrence. Larger metacentric studies integrating molecular profiling are needed to better define prognostic markers and therapeutic strategies for these rare neoplasms.